COMPARISON OF CRUSTAL DEFORMATION RATES ESTIMATED FROM SEISMIC AND GPS DATA ON THE BISHKEK GEODYNAMIC POLYGON - N. A. Sycheva; A. N. Mansurov (Геодинамика и тектонофизика)
The Bishkek geodynamic polygon (BGP, 41.5–43.5° N – 73–77° E) is located within the central segment of the North Tien Shan seismic zone, in the junction zone of the Tien Shanorogene and the Turan plate (Fig. 1). In the entire modern structure of Tien Shan lengthwise zones of shearing (with both right- and left-lateral strike-slip faults) are observed, thus Tien Shancan be considered as a transpression zone. Our study aimed at comparing deformation values estimated for the BGP territory from the seismic and GPS data. The modern stress-strain state of the study area was determined from the focal mechanisms of 1287 earthquakes that occurred in the period from 1994 to 2015. The study area was divided into cells with a radius of 0.2° (~20 km). The cell centers were in the nodes of the grid with a spacing of 0.1° (~10 km). A tensor of a seismotectonic deformation (STD) rate within a cell was calculated as a sum of seismic moment tensors normalized for time, volume and shear modulus, assuming that STD is similar at different scale levels. The STD field is shown in Figure 4 at the background given by the deformation intensity pattern. Figure 6 shows the scatter of the sums of the strain rate tensor’s horizontal components estimated from the seismic data. The modern crustal movements were estimated from the geodetic measurements performed on the Central Asian GPS Network. Using the crustal movement velocities for 90 sites in the study area, the deformation processes in the crust were modeled based on the linear part of the Taylorexpansion of the point's-velocity-versus-its-radius-vector function. Then the velocity gradient tensors were estimated for the grid nodes with a spacing of 8.3 km. To estimate tensor's value in every single grid node a system of linear algebraic equations was solved by the weighted least-squares method. The weight of an observation point decreased with an increasing distance to such point, so that the inhomogeneity of the deformation field could be taken into account. From the velocity gradient tensors we calculate the strain rate tensors (Fig. 5) and then the rate of changes of the area (meterage)  (Fig. 7). A comparison of Figures 4 and 5 shows a general coincidence between the directions of compression/shortening axes estimated from the seismic and GPS data. On average, the STD intensity is by two to three orders lower than the deformation intensity assessed from the GPS data. It can be explained by the fact that the horizontal components of the total deformation amounts visible in the GPS data are actually the sums of aseismic and coseismic components, and the deviator part of coseismic component was considered as STD. Comparing the fields of the sums of the strain rate tensor’s horizontal components from the seismic data (Fig. 6) and the GPS data (Fig. 7) reveals an inconsistency for the Suusamyr depression: the GPS data shows a considerable crustal shortening in the horizontal plane, while the seismic data is indicative of a shear deformation. In the central part of the junction zone of the Chu basin and the Kyrgyz ridge, the crustal shortening rate exceeds –50·10–9 per year, and it is likely that the stress is released by seismicity of a low magnitude, which can be induced by the operations of an electromagnetic prospecting generator in this territory.